2018
DOI: 10.1111/febs.14668
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐limiting step and substrate accessibility of cellobiohydrolase Cel6A from Trichoderma reesei

Abstract: The cellobiohydrolase (CBH) Cel6A is an important component of enzyme cocktails for industrial degradation of lignocellulosic biomass. However, the kinetics of this enzyme acting on its natural, insoluble substrate remains sparsely investigated. Here, we studied Cel6A from Trichoderma reesei with respect to adsorption, processivity, and kinetics both in the steady‐state and pre‐steady‐state regimes, on microcrystalline and amorphous cellulose. We found that slow dissociation (koff) was limiting the overall rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
2
20
0
4
Order By: Relevance
“…The biological basis of the molecular selection for processivity across a wide range of Group 5 members is not immediately intuited. Processivity is generally considered to be advantageous for enzymes acting on crystalline substrates such as cellulose or chitin, where initial chain engagement is thought to be rate-limiting (42)(43)(44)(45)(46)(47). However, this would not be expected for soluble polysaccharides, such as XyG, especially under dilute assay conditions in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological basis of the molecular selection for processivity across a wide range of Group 5 members is not immediately intuited. Processivity is generally considered to be advantageous for enzymes acting on crystalline substrates such as cellulose or chitin, where initial chain engagement is thought to be rate-limiting (42)(43)(44)(45)(46)(47). However, this would not be expected for soluble polysaccharides, such as XyG, especially under dilute assay conditions in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Endoxyloglucanases can be further delineated into endo-dissociative enzymes, which hydrolyze the backbone and immediately release both new chain ends, and endo-processive enzymes, which perform multiple hydrolytic events, releasing short oligosaccharides before disengaging. The ability of some GH74 enzymes (26,28,29,35) to act processively on soluble XyG is notable, considering that this mode of action is more commonly associated with GHs acting on crystalline cellulose or chitin (42)(43)(44)(45)(46)(47).…”
mentioning
confidence: 99%
“…This has the noticeable consequence that the free energy of the (rate-limiting) TS is quite similar for all tested enzymes, and that the main kinetic diversity lies in different affinities for the substrate. Experimental studies have suggested that the ratelimiting step for some cellulases is slow dissociation [32][33][34][35][36] . Since weaker binding is associated with a lower activation barrier for dissociation ( Fig 5B-3), a dissociation limited mechanism would explain the inverse correlation of binding strength and maximal turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme activity and binding a nity were measured on three different cellulosic substrates: regenerated amorphous cellulose (RAC), Avicel PH101 (Sigma-Aldrich, St. Louis, MO) and bacterial microcrystalline cellulose (BMCC). RAC was prepared from Avicel as described earlier [39,40]. BMCC was prepared from bacterial cellulose (BC) as described in [34,35].…”
Section: Substratesmentioning
confidence: 99%